Trust, Power, and Partnership: A Study of the Evolution of Sweden’s Bilateral Economic Partnership with Post-Apartheid South Africa - Tove Sternehäll (The Thinker)
In This article examines the legacy of the Swedish antiapartheid movement on their post-apartheid bilateral economic relationship with South Africa. Focusing on developments within the South African economy from a Swedish perspective, the article studies Sweden’s ambitions and efforts to develop their economic cooperation. The study is built on mixed methods where the main bulk of data is collected through semistructured interviews with Swedish experts on the bilateral relationship. Through an analytical framework built on embeddedness theory and soft power, the article examines the impact of the trust and influence that stems from Sweden’s support of the South African liberation movement.